Computational and Bioinformatics Frameworks for Next-Generation Whole Exome and Genome Sequencing - Marisa P. Dolled-Filhart; Michael Lee; Chih-wen Ou-yang; Rajini Rani Haraksingh; Jimmy Cheng-Ho Lin (The Scientific World Journal)
It has become increasingly apparent that one of the major hurdles in the genomic age will be the bioinformatics challenges of next-generation sequencing. We provide an overview of a general framework of bioinformatics analysis. For each of the three stages of (1) alignment, (2) variant calling, and (3) filtering and annotation, we describe the analysis required and survey the different software packages that are used. Furthermore, we discuss possible future developments as data sources grow and highlight opportunities for new bioinformatics tools to be developed.